STUDY OF ARCHITECTURAL CONCERNS ON DESIGN PRINCIPLES IN THE CATHOLIC CHURCH OF PURBALINGGA - Yohanes Wahyu Dwi Yudono; Susatyo Adhi Pramono (Fakultas Teknik Universitas Wijayakusuma Purwokerto, 2019)
Overall, the shape of the Purbalingga Catholic church building displays the style / style of Javanesearchitecture (Joglo). However, in an effort to